PENGARUH INTENSITAS KEIKUTSERTAAN DALAM OSIS TERHADAP HASIL BELAJAR SISWA - Nur Aisyah Agustin Bakhri; Martin Kustati; Nana Sepriyanti (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to determine the effect of the intensity of participation in the Student Organization Intra School (OSIS) on students' learning outcomes. This research was conducted at SMA Negeri 16 Padang, with a sample of 48 students who participated in the Student Organization Intra School (OSIS) activities. The research method used in this study is an Ex Post Facto quantitative research designed with a cross-sectional design. The data collection techniques in this study are observation, questionnaires, and documentation. The research instrument uses a Likert scale questionnaire to measure the intensity of participation in the student council (OSIS), while learning outcomes are measured thru report card grades for the second semester of the 2024/2025 academic year. The research results show a positive and significant influence of participation intensity in the student council (OSIS) on students' academic performance with a percentage of 46.8%. Considering the hypothesis test results, we found that H0 was rejected and Ha was accepted.